2017
DOI: 10.1007/s11012-017-0789-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between oblique waves and multiple bottom-standing flexible porous barriers near a rigid wall

Abstract: The interaction between oblique surface waves and multiple bottom-standing flexible porous barriers under the combined effects of a neighboring rigid vertical wall and a step of arbitrary profile on the bottom is investigated. The problem is analyzed under the assumptions of small-amplitude water waves and structural response. The solutions are found using the methods of least-squares approximation, eigenfunction expansion and multi-mode approximation associated with the modified mild-slope equation. To keep t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The study suggested that the bottom standing barriers are acceptable as breakwaters, and free clamped barriers performance is significant as compared with moored clamped barriers to attenuate the maximum wave energy. Behera and Ng (2018), Kaligatla et al (2018) extended the study considering variation in the seabed characteristics in the wave reflected region. Very recently, Somervell et al (2018) proposed a simplified empirical relation to find the friction factor with known parameters like porosity, width and depth of the structure using the eigenfunction expansion method.…”
Section: Introductionmentioning
confidence: 99%
“…The study suggested that the bottom standing barriers are acceptable as breakwaters, and free clamped barriers performance is significant as compared with moored clamped barriers to attenuate the maximum wave energy. Behera and Ng (2018), Kaligatla et al (2018) extended the study considering variation in the seabed characteristics in the wave reflected region. Very recently, Somervell et al (2018) proposed a simplified empirical relation to find the friction factor with known parameters like porosity, width and depth of the structure using the eigenfunction expansion method.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the continuity of velocity as in equation (9) and the orthogonality of open water eigenfunctions along with the barrier and gap region in equations (23) and (24) at r = r 1 yields…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…Similarly, substituting the potentials (equations (23) and (24)) in pressure continuity as in equation 10yields…”
Section: Methods Of Solutionmentioning
confidence: 99%
See 2 more Smart Citations